Męczennicy jezuiccy w Żywotach świętych Piotra Skargi - Albingier, Elżbieta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
This article is an attempt to analyze the functions, which Piotr Skarga gives in parts of Żywoty świetych focused on the martyrdom of Jesuits. Their biographies can be considered as the argument in the current debate on true and false martyrdom. Skarga, referring to the authority of The Bible and the works of the Church fathers, tried to prove that only the Catholic martyrs are the true ones. Persecutions of Jesuits in England, France, and during the missions to India and to the Americas are also an opportunity for Skarga to show how groundless the allegations are against the Jesuits. In the Polish–Lithuanian Commonwealth, they were accused of pernicious influence on king’s political decisions and greed. Author of Żywoty świętych, using the examples from the life and martyrdom of Jesuits attempted to rehabilitate the opinion of his order.